2017
DOI: 10.1016/j.jri.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of NLRP3 inflammasome in placentas from pregnant women with severe preeclampsia

Abstract: Preeclampsia is a pregnancy disorder characterized by imbalance between pro- and anti-inflammatory cytokines associated with high plasma levels of uric acid and Interleukin-1 beta (IL-1β). The inflammasome is a protein complex that mediates innate immune responses via caspase-1 activation promoting secretion of IL-1β and IL-18 in their active forms, and also release of the high-mobility group box 1 protein (HMGB1). As the placenta seems to play an important role in the pathogenesis of PE, the present study inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
89
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(104 citation statements)
references
References 36 publications
14
89
0
1
Order By: Relevance
“…The cell-specific co-localization of components essential for NLRP3 activity strongly supports a link between complement priming, NLRP3 inflammasome activation and IL-1b production in the syncytiotrophoblast. Our findings are sustained in a recent report showing NLRP3, caspase-1 and IL-1b protein expression in the syncytiotrophoblast layer [32] and by NLRP3 expression in placental lysates and primary trophoblasts [31,33,34,45,46]. Syncytium IL-1b production in first-and third-trimester placentas is in accordance with previous findings [47][48][49].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The cell-specific co-localization of components essential for NLRP3 activity strongly supports a link between complement priming, NLRP3 inflammasome activation and IL-1b production in the syncytiotrophoblast. Our findings are sustained in a recent report showing NLRP3, caspase-1 and IL-1b protein expression in the syncytiotrophoblast layer [32] and by NLRP3 expression in placental lysates and primary trophoblasts [31,33,34,45,46]. Syncytium IL-1b production in first-and third-trimester placentas is in accordance with previous findings [47][48][49].…”
Section: Discussionsupporting
confidence: 93%
“…Studies of the NLRP3 inflammasome pathway in pre-eclampsia are limited. Recently, Weel et al [32] showed elevated NLRP3 and caspase-1 in placental tissue from pre-eclamptic pregnancies; however, our study is the first to quantify cell-specific NLRP3 protein expression in the syncytiotrophoblast layer. Our identification of elevated placental IL-1b expression in pre-eclampsia is in accordance with previous findings [31,32,50].…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations